(untitled) (Journal of Scientific Research, 2011)
This work reports a theoretical investigation of π-conjugated oligomers constituted by n units (n = 1-4) based on carbazole and ethylenedioxythiophene. The molecular geometry, torsional potential, electronic and optical properties of the oligomers [Cbz-(Edot)n-Cbz] (n = 1-4) are investigated using DFT (B3LYP/3-21G*) calculations. The discussion is focused on the influence of chain length on the properties of these copolymers. The analyses of torsional angles for [Cbz-(Edot)4-Cbz] reveal that the structure has a anti-planar conformation. The electronic properties of the molecules, HOMO, LUMO and Eg (HOMO-LUMO), are studied using B3LYP functional. The results have been compared with those of thiophene and ethylenedioxythiophene. The lowest excitation energies (Eex) and the maximal absorption wavelength (λabs) are studied using the TD/DFT, ZINDO and CIS methods. The electronic transitions of the absorption spectrum derived by TD/DFT method give useful structural and electronic information for designing novel conducting organic polymer materials. The bridging effect by C=C(CN)2 on the optoelectronic properties of the (carbazole-thiophene-carbazole) comonomer is investigated. Keywords: Conducting polymer; Carbazole-(Ethylenedioxythiophene)n-Carbazole comonomers; DFT Optoelectronic properties; absorption coefficient; Bridging effect. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i1.7450 J. Sci. Res. 4 (1), 119-133 (2012)